Pueblo Mapuche : Ensayos por un Chile plurinacional - Mesías, Augusto Samaniego (Santiago, Chile Ariadna Ediciones, 2020)
Political and historical essays on the Mapuche population in Chile and its recognition as a nation
Spanish
Keywords: Social & cultural history; Mapuche population; recognition of rights; nation; indigenous political action